Numerical and experimental investigation for hybrid Photovoltaic/thermal collector system in Duhok city - Khaled, Semyan; Ali, Omar (Journal of Environmental Engineering and Landscape Management, 2020)
The study deals with the experimental and numerical investigation of the hybrid Photovoltaic-thermal solar collector system in Duhok city during seven months and includes different measurements of temperatures, water mass flow rate, wind velocity, and solar intensity. A one-dimensional mathematical model is used to simulate the transient processes with constant thermo-physical properties and heat transfer coefficients. The energy conservation equations are solved using implicit finite difference method. The numerical and experimental results showed satisfactory agreement with an error (2.36%) between two thermal efficiencies. The results include the estimation of the electrical and thermal energy, thermal, electrical and overall efficiency. The highest overall efficiency of PV/T collector occurs in May 2019 with value (72.01%) and the lowest value in January 2019 is obtained as (63.1%). The cooling method leads to an increase in the electrical efficiency to about 3% as compared with PV solar collector system.